THE VIRTUAL LEARNING DURING COVID 19 PANDEMIC: WHAT ARE STUDENTS BELIEF ON IT? - Dodi Erwin Prasetyo (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
There were exceedingly rare researches in analysing students’ gender differences of internet beliefs for Indonesia context. Therefore, this study was aimed at describing students’ beliefs of the internet usage, and at gauging male and female students’ differences on the internet beliefs. This study employed 27 students in East Java (6 male and 21 female). The study data was via questionnaire and gauged in MS Excel and SPSS 25. Hence, this study used quantitative descriptive to explain students beliefs on the internet usage in learning. While measuring differences based on the gender, the researcher used Mann Whitney analysis. Results diagnosed that most of students gained positive beliefs for the internet usage in their learning. However, there were no significant differences because of significance two tailed value upper than .05. It could be assumed both gender students have in similar line beliefs on the internet usage for their learning. Fruitful suggestions are recommended, due to the pedagogic and future research aspect. For pedagogical aspect, the internet should be elaborated and integrated extensively in the learning instruments as well as learning materials to develop better process and outputs. For future research, those findings can be used to explore more for other study fields.